The Role of Mfsd2a in Nervous System Diseases - Huang, Bei; Li, Xihong (Frontiers in Neuroscience, 2021)
Major facilitator superfamily (MFS) is the maximum and most diverse membrane transporter, acting as uniporters, symporters and antiporters. MFS is considered to have a good development potential in the transport of drugs for the treatment of brain diseases. The major facilitator superfamily domain containing protein 2a (Mfsd2a) is a member of MFS. Mfsd2a-knockout mice have shown a marked decrease of docosahexaenoic acid (DHA) level in brain, neuron loss, microcephaly and cognitive deficits. Mfsd2a has attracted more and more attention in the study of nervous system diseases because of its crucial role in maintaining the integrity of the blood-brain barrier (BBB) and transporting DHA, including inhibiting cell transport in central nervous system endothelial cells, alleviating BBB injury, avoiding BBB injury in cerebral hemorrhage model, acting as a carrier etc. Up to now, the clinical research of Mfsd2a in nervous system diseases is rare. This article reviewed the current research progress of Mfsd2a in nervous system diseases. It summarized the physiological functions of Mfsd2a in the occurrence and development of intracranial hemorrhage (ICH), Alzheimer's disease (AD), sepsis-associated encephalopathy (SAE), autosomal recessive primary microcephaly (MCPH) and intracranial tumor, aiming to provide ideas for the basic research and clinical application of Mfsd2a.